GREEN BANKING INITIATIVES IN AZERBAIJAN: CONTRIBUTION OF FINANCIAL SYSTEM - Nazrin Akhundzada; Inara Rzayeva (Agora International Journal of Economical Sciences)
Based on existing academic literature, green banking can primarily evolve along three directions: green product development, green corporate social responsibility, and green internal processes This study qualitatively evaluates the commitment of seven top-performing banks in Azerbaijan to green banking initiatives and categorizes their activities across these dimensions. The results of the content analysis illustrate that the banks under study demonstrated the strongest commitment in the areas of green products and corporate social responsibility. The adoption of green banking practices is anticipated to expand within the banking sector of Azerbaijan in the foreseeable future. Moreover, this article empirically examines the impact of environmental performance, primarily related to the internal processing category of business operations and assessed by resource consumption, on the profitability of the top two banks in Azerbaijan. The results reveal that, after controlling for bank size, environmental indicators do not exert a statistically significant impact, either positive or negative, on the profitability of these banks. Notably, energy consumption and GHG emissions exhibited the most considerable negative association, while only water consumption demonstrated a positive relationship with profitability. These findings support the tenets of Legitimacy theory and align with the findings of previous studies.